Cognitive dissonance in health insurance consumers: Analysis through financial literacy - Diana Anggraini; Rudi Sukandar; Chawla Fatmaduri (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2026)
The low public participation in health insurance in Indonesia is influenced not only by economic barriers but also by psychological factors. This study aims to examine the role of cognitive dissonance in health insurance purchasing decisions and to analyze how financial literacy reduces psychological tension among consumers. Using a mixed-methods approach with an exploratory sequential design, the qualitative phase was conducted through in-depth interviews, while the quantitative phase involved survey data from 290 respondents analyzed using SmartPLS. The findings indicate that cognitive dissonance positively influences financial literacy, while financial literacy negatively affects behavioral intention and post-purchase dissonance. These results highlight the importance of financial literacy in helping consumers develop more rational perceptions of insurance premiums, benefits, and claims processes, thereby reducing regret and dissatisfaction after purchase. This study concludes that effective communication strategies and financial literacy education can play a crucial role in increasing public participation in Indonesia's health insurance.